Myogenesis in insect metamorphosis as a substrate for the development of muscle-based actuators - Ludwig, Jacqueline. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Biology.; Advisor: Barry Trimmer.; Committee: Kelly McLaughlin, and Eric Tytell.; Keywords: Biology, Developmental biology, and Entomology.